The teacher acting as mediator in new technologies use: a case study in physics teaching - Almeida Valiati, Eliane Regina de (2005)
Nowadays, the new technologies challenge the educational practices. When teachers face this new teaching and learning pattern they need to adopt a different attitude: of a mediator, in which one its main role is to experience and mediate processes of learning construction proportioned and encouraged by the increasing inclusion of New Communication and Information Technologies (NCTIs) at schools. This paper presents the results obtained in a research which objective was to evaluate the use of different methodologies and resources in the teaching and learning process in Physics, questioning the approaches used in the Physics teaching, their pedagogical inferences, didactic resources and the teacher’s role when using these new technologies as well